Retrospective analysis of a case series of patients with traumatic injuries to the craniocervical junction - Esteves,Luiz Adriano (2016)
ABSTRACT Objective To evaluate the correlation between the treatment, the characteristics of the lesions and the clinical outcome of patients with traumatic injuries to the craniocervical junction. Methods This was a retrospective study of patients treated conservatively or surgically between 2010 and 2013 with complete data sets. Results We analyzed 37 patients, 73% were men with mean age of 41.7 years. Of these, 32% were submitted to initial surgical treatment and 68% received conservative treatment. Seven (29%) underwent surgery subsequently. In the surgical group, there were seven cases of odontoid type II fractures, two cases of fracture of posterior elements of the axis, one case of C1-C2 dislocation with associated fractured C2, one case of occipitocervical dislocation, and one case of combined C1 and C2 fractures, and facet dislocation. Only one patient had neurological déficit that improved after treatment. Two surgical complications were seen: a liquoric fistula and one surgical wound infection (reaproached). In the group treated conservatively, odontoid fractures (eight cases) and fractures of the posterior elements of C2 (five cases) were more frequent. In two cases, in addition to the injuries of the craniocervical junction, there were fractures in other segments of the spine. None of the patients who underwent conservative treatment presented neurological deterioration. Conclusion Although injuries of craniocervical junction are relatively rare, they usually involve fractures of the odontoid and the posterior elements of the axis. Our results recommend early surgical treatment for type II odontoid fractures and ligament injuries, the conservative treatment for other injuries.